[Paid ambushes ; Destruction of Mines View Park ; Norman Black [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
An investigative look at BBC newsman's revelation that ambuses can be staged for a fee. Ecological/political story of city planning gone haywire in a national park in Baguio City. A look at basketball "imports" in Philippine basketball league.